Implementation of Picture Description Method through Picture Banner Media in Arabic Language Learning - Inayah, Ine Inayah; Ningsih, Ayu Widya; Mawaddah, Abdilah Lina Afifah; Hanifah, Umi; Anam, Khoirul (Jurusan Pendidikan Bahasa Arab Fakultas Tarbiyah dan Keguruan Institut Agama Islam Negeri Sultan Maulana Hasanuddin, 2023)
Implementing media in education is needed to improve the quality of the process and student learning outcomes, including in Arabic language learning. This study aims to explore how the implementation of the image description method using pictorial banner media in Arabic language learning, especially in learning listening and speaking skills. This research uses descriptive qualitative research methods. The study was conducted at one of the MTsN in the Sidoarjo city area, East Java, with a sample size of 33 students. Data collection techniques in this study were observation, interviews, and documentation. Data analysis was carried out through several stages: data collection stage, data reduction, data presentation, data verification, and data summarization. The results showed that the implementation of the image description method using banner media in Arabic language learning was able to improve students' Maharah al-Kalam, train students Maharah al-istima', make it easier for students to memorize microdata, and make it easier for teachers to identify each student's listening skills and speaking skills.